2019
DOI: 10.1016/j.artd.2019.05.001
|View full text |Cite
|
Sign up to set email alerts
|

Cementation of a monoblock dual mobility bearing in a newly implanted porous revision acetabular component in patients undergoing revision total hip arthroplasty

Abstract: Background: The most common indications for revision total hip arthroplasty are instability/dislocation and mechanical loosening. Efforts to address this have included the use of dual mobility (DM) articulations. The aim of this study is to report on the use of cemented DM cups in complex acetabular revision total hip arthroplasty cases with a high risk of recurrent instability. Methods: A multicenter, retrospective study was conducted. Patients who received a novel acetabular construct consisting of a monoblo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
19
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(19 citation statements)
references
References 38 publications
0
19
0
Order By: Relevance
“…Most of the shells used in our study were of tantalum TM structure, which, theoretically, might provide more fixation strength, given the characteristics of tantalum. In a series of 38 patients, Gabor et al [ 29 ] performed the acetabular construction including a monoblock dual mobility cup cemented into a fully porous metal shell. No patients needed reoperation due to loosening of the acetabular component after 7 months, and the HHS improved from 50 ± 12 to 78 ± 11.…”
Section: Discussionmentioning
confidence: 99%
“…Most of the shells used in our study were of tantalum TM structure, which, theoretically, might provide more fixation strength, given the characteristics of tantalum. In a series of 38 patients, Gabor et al [ 29 ] performed the acetabular construction including a monoblock dual mobility cup cemented into a fully porous metal shell. No patients needed reoperation due to loosening of the acetabular component after 7 months, and the HHS improved from 50 ± 12 to 78 ± 11.…”
Section: Discussionmentioning
confidence: 99%
“…Gabor et al, in their retrospective case series of 38 patients with acetabular bone loss ranging from Paprosky type IIA to IIIB, reported a dislocation rate of 2.6% at a mean follow up of 7 months after revision THA with a monoblock DM cup cemented into a fully porous revision acetabular shell. 22 Similarly, Schneider et al reported 10.4% dislocation rate in their retrospective case series of 96 patients with severe acetabular bone loss who underwent revision THA with DM cups cemented into antiprotrusio cages. 23 Their study included very complex cases with 90% of the included patients having severe acetabular defects (SOFCOT III & IV), 35% of the cases having had prior revision, and most of them needing allograft.…”
Section: Revision With Extensive Acetabular Bone Lossmentioning
confidence: 92%
“…6,7 While poor acetabular component position may predispose a patient to recurrent instability after revision THA, the removal of well-fixed yet sub-optimally placed shells is associated with significant morbidity and bone loss. 5,8,9 Therefore, the cementation of the outer metallic liner of DM cups to a well-fixed acetabular shell (metal-in-metal constructs), also known as the double socket technique, is an alternative that has progressively gained recognition. 5,8,10 This technique allows partial correction of the acetabular position and orientation.…”
Section: Introductionmentioning
confidence: 99%
“…5,8,9 Therefore, the cementation of the outer metallic liner of DM cups to a well-fixed acetabular shell (metal-in-metal constructs), also known as the double socket technique, is an alternative that has progressively gained recognition. 5,8,10 This technique allows partial correction of the acetabular position and orientation. The double socket technique introduces a cement layer between the metallic liner and the acetabular shell, which creates an additional interface with an inherent potential for failure.…”
Section: Introductionmentioning
confidence: 99%